A review on the provisions in the penal code regarding baby dumping: punishment V. Rehabilitation / Siti Syarfa Alhabshee - Alhabshee, Siti Syarfa; Mohmad Nor, Noraidah; Ahmad Fauzi, Nurul Afiqah (Faculty of Law, 2012)
This research is based on the necessity to find out the reasons behind the rise of baby dumping cases in Malaysia and the provisions of the law that governs it, whether effective or otherwise. The law that governs this issue is laid down in Section 317 and Section 318 of the penal code. This provisions deals with abandonment and concealment of baby. In examining the law in Malaysia, comparisons are made with other countries such as China, United States of America and South Africa. Comparisons are made to find out as to the best form of punishment for this offender. Rehabilitation has been gaining momentum in the trend of punishing baby dumping offenders. This research is to determine the most effective punishment for this offence by reviewing the provisions that govern it presently and whether stricter punishment needs to be implement or other alternative punishment need to be considered.